ANALISIS PENGARUH SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PENGELOLAAN PERSEDIAAN OBAT (Studi Kasus Pada Karyawan Rumah Sakit SMC Telogorejo Semarang) - Julius Khrisna Pratama; Imam Ghozali (Diponegoro Journal of Accounting, 2025)
Effective management of drug inventory is one of the key factors in supporting the continuity of hospital services. However, in practice, many hospitals face various challenges in optimizing drug inventory management, which are often related to the suboptimal implementation of accounting information systems and weak internal controls. Therefore, this study aims to analyze the influence of accounting information systems and internal control on the effectiveness of drug inventory management at Telogorejo Hospital.This study employs a quantitative approach with a causal-comparative research design. Primary data were collected through the distribution of questionnaires to 94 respondents directly involved in drug inventory management. The data analysis technique used is multiple linear regression, assisted by SPSS version 26 software.Partially, both variables also have a significant positive influence. These findings indicate that the better the accounting information system and the stronger the internal control implemented, the higher the effectiveness of drug inventory management.